Enforcing IPR through informal institutions: The possible role of religion in fighting software piracy - Nora Elbialy; Moamen Gouda (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
The existence of formal IPR laws can be considered a prerequisite for having efficient law enforcement but does not imply efficient enforcement in itself. A simple model is constructed to explain the interplay between the IPR law and human behavior within counterfeiting countries. It shows how a politically monitored IPR enforcement strategy is able to alter formal IPR laws or institutions but might not affect informal institutions, or human morals and behavior, to the same extent, hence barely affecting piracy situation. The model shows the essential role of informal institutions and its sanction mechanisms in the enforcement process. The main obstacle of IPR enforcement is that people are still not convinced that IPR violations are unethical. Religion can be considered an informal institution that might support or hinder formal laws issued with regards to IPR and hence influence de facto enforcement of laws, especially in countries with high piracy rate if a high adherence to religion is found. As the Religion-Loyalty Index (RLI) developed by this study shows, Muslim countries have the highest religiosity level among different religions. Consequently, an investigation of how Islamic jurisprudence views IPR piracy is conducted. As Islam generally prohibits IPR piracy, a set of policy recommendations based on new institutional perspective is presented that can effectively help in minimizing IPR piracy in developing countries in general and Muslim ones in specific.
Keywords: F19; K39; K42; L86; Z12; 330; Intellectual Property Rights (IPR); formal vs. informal institutions; New Institutional Economics (NIE); software piracy; religion; enforcement; Immaterialgüterrechte; Normbefolgung; Religion; Islam; Software; Produktpiraterie; Entwicklungsländer; Islamische Staaten